ALOS-2/PALSAR-2 Calibration, Validation, Science and Applications - Tadono, Takeo; Ohki, Masato (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Twelve edited original papers on the latest and state-of-art results of topics ranging from calibration, validation, and science to a wide range of applications using ALOS-2/PALSAR-2. We hope you will find them useful for your future research.